2013
DOI: 10.1111/nhs.12087
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a new instrument for testing functional health literacy in Japanese adults

Abstract: This study aimed to develop a reliable and valid measure of functional health literacy in a Japanese clinical setting. Test development consisted of three phases: generation of an item pool, consultation with experts to assess content validity, and comparison with external criteria (the Japanese Health Knowledge Test) to assess criterion validity. A trial version of the test was administered to 535 Japanese outpatients. Internal consistency reliability, calculated by Cronbach's alpha, was 0.81, and concurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Similarly, issues of cultural equivalency was noted as a challenge in translating “TOFHLA-like” measures since some items on the TOFHLA are specific to healthcare in the US. As a result, new HL measures for specific cultural/linguistic groups within and outside the US emerged in the literature over the last few years [41,42,45,52,55,56,61,64,65,67,83,84,87,88,90,92,97,101,102,106,108,110]. Among these 37 non-English language measures, only two specified the racial/ethnic characteristics of their sample beyond simply describing the general population in which the measure was being validated [35,64].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, issues of cultural equivalency was noted as a challenge in translating “TOFHLA-like” measures since some items on the TOFHLA are specific to healthcare in the US. As a result, new HL measures for specific cultural/linguistic groups within and outside the US emerged in the literature over the last few years [41,42,45,52,55,56,61,64,65,67,83,84,87,88,90,92,97,101,102,106,108,110]. Among these 37 non-English language measures, only two specified the racial/ethnic characteristics of their sample beyond simply describing the general population in which the measure was being validated [35,64].…”
Section: Resultsmentioning
confidence: 99%
“…With regards to the psychometric properties of the HL measures, the majority of measures ( n = 83, 89%) used analysis consistent with Classical Test Theory (CTT) for reliability testing and/or item reduction, while a small but growing number reported using analysis consistent with newer advanced approaches such as Rasch and Item Response Theory (IRT) either alone or adjunctively( n = 16, 15%) with CTT [4,27,28,39,47,52,54,56,61,62,64,67,78,101,108]. The reported reliability was generally strong across most measures (Cronbach’s a or KR-20 = 0.70–0.98), with the exception of a few measures [64,65,81,107].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, China's health literacy level is still low. Previous studies have shown that the proportions of people with adequate health literacy in the United States, the United Kingdom and Japan were 64%, 88.6% and 72.3%, respectively [14,18,19]. In terms of scores on different dimensions, the participants' scores in the dimension of BKA were higher than those in the dimension of HLB.…”
Section: Discussionmentioning
confidence: 93%
“…However, compared with some developed countries of equal economic development, China's health literacy level is still low. Previous studies have shown that the proportions of people with adequate health literacy in the United States, the United Kingdom and Japan were 64%, 88.6% and 72.3%, respectively [11,14,15]. In terms of scores on different dimensions, the proportion of respondents with basic knowledge and attitudes was higher than those with healthy lifestyles and behaviours.…”
Section: Discussion Health Literacy Level and Its Distribution Characmentioning
confidence: 96%